Cultivation of medicinal herbs as successful model for development of hilly-mountainous regions of Serbia - Maletić, Radojka; Popović, Blaženka; Janković-Šoja, Svjetlana (Economics of Agriculture, 2010)
Thanks to the favourable climate, soil and unpolluted environment, Serbia is very suitable for intensive cultivation of medicinal herbs and has long tradition in this activity. Their production generates higher, faster and easier proft than any other agricultural crop. Relevance of issues relating to new resources of medicinal herbs imposes new obligations pertaining to fnding of new possibilities of increased production of medicinal herbs in the World, in order to balance the relation between increasing demand for this valuable raw material and relatively limited supply on the market. Diversity of soil-climatic factors, as well as the production on various altitudes (even extremely high ones), are objective basis of successful plantation production of medicinal herbs in the Republic of Serbia. Despite the fact that cultivation of medicinal herbs is great investment since it generates several times greater income per hectare compared to corn or wheat, annually only between 1300 and 1800 ha of medicinal herbs are planted in Serbia. European market shows constant interest in high quality medicinal herbs originating from our territories, which would ensure to business operators in perspective signifcant fnancial results. Incentive measures of the Ministry of Agriculture, forestry and Water Management directed towards cultivation of medicinal herbs would signifcantly contribute to development of hilly-mountainous regions, as well as entire rural community of the Republic of Serbia (Ceranić, et al. 2005; Popović, 2008). Sustainable development of natural resources of medicinal and spice herbs is directly dependant on implementation and improvement of the legislation and standards which need to be harmonized with EU legislation and standards. Regardless of the great potentials of the herbal sector within the economical system of the country, many potential, especially in regard to export, higher stages of processing and cultivation of medicinal herbs (especially based on principles of organic production) have not been exploited.